The use of breast conserving surgery: linking insurance claims with tumor registry data - Maskarinec, Gertraud (BioMed Central, 2002)
BACKGROUND: The purpose of this study was to use insurance claims and tumor registry data to examine determinants of breast conserving surgery (BCS) in women with early stage breast cancer. METHODS: Breast cancer cases registered in the Hawaii Tumor Registry (HTR) from 1995 to 1998 were linked with insurance claims from a local health plan. We identified 722 breast cancer cases with stage I and II disease. Surgical treatment patterns and comorbidities were identified using diagnostic and procedural codes in the claims data. The HTR database provided information on demographics and disease characteristics. We used logistic regression to assess determinants of BCS vs. mastectomy. RESULTS: The linked data set represented 32.8% of all early stage breast cancer cases recorded in the HTR during the study period. Due to the nature of the health plan, 79% of the cases were younger than 65 years. Women with early stage breast cancer living on Oahu were 70% more likely to receive BCS than women living on the outer islands. In the univariate analysis, older age at diagnosis, lower tumor stage, smaller tumor size, and well-differentiated tumor grade were related to receiving BCS. Ethnicity, comorbidity count, menopausal and marital status were not associated with treatment type. CONCLUSIONS: In addition to developing solutions that facilitate access to radiation facilities for breast cancer patients residing in remote locations, future qualitative research may help to elucidate how women and oncologists choose between BCS and mastectomy.